Early Multicenter Experience With Imipenem-Cilastatin-Relebactam for Multidrug-Resistant Gram-Negative Infections. (9th December 2021) - Rebold, Nicholas; Morrisette, Taylor; Lagnf, Abdalhamid M; Alosaimy, Sara; Holger, Dana; Barber, Katie; Justo, Julie Ann; Antosz, Kayla; Carlson, Travis J; Frens, Jeremy J; Biagi, Mark; Kufel, Wesley D; et al.
Abstract: A multicenter case series of 21 patients were treated with imipenem-cilastatin-relebactam. There were mixed infection sources, with pulmonary infections (11/21, 52%) composing the majority. The primary pathogen was Pseudomonas aeruginosa (16/21, 76%), and 15/16 (94%) isolates were multidrug-resistant. Thirty-day survival occurred in 14/21 (67%) patients. Two patients experienced adverse effects.